Wittgenstein within the Philosophy of Religion - Carroll, Thomas D. author. aut Link
X, 209 p.
Keywords: The commonly held view that Wittgensteinian philosophy of religion is fideistic loses plausibility when contrasted with recent scholarship on Wittgenstein's corpus and biography. This book reevaluates the place of Wittgenstein in the philosophy of religion and charts a path forward for the subfield by advancing three themes.